Time‐lapse photogrammetry reveals hydrological controls of fine‐scale High‐Arctic glacier surface roughness evolution. Issue 6 (23rd February 2022) - Irvine‐Fynn, Tristram D. L.; Holt, Tom O.; James, Timothy D.; Smith, Mark W.; Rutter, Nick; Porter, Philip R.; Hodson, Andrew J.
Abstract: In a warming Arctic, as glacier snowlines rise, short‐ to medium‐term increases in seasonal bare‐ice extent are forecast for the next few decades. These changes will enhance the importance of turbulent energy fluxes for surface ablation and glacier mass balance. Turbulent energy exchanges at the ice surface are conditioned by its topography, or roughness, which has been hypothesized to be controlled by supraglacial hydrology at the glacier scale. However, current understanding of the dynamics in surface topography, and the role of drainage development, remains incomplete, particularly for the transition between seasonal snow cover and well‐developed, weathered bare‐ice. Using time‐lapse photogrammetry, we report a daily timeseries of fine (millimetre)‐scale supraglacial topography at a 2 m 2 plot on the Lower Foxfonna glacier, Svalbard, over two 9‐day periods in 2011. We show traditional kernel‐based morphometric descriptions of roughness were ineffective in describing temporal change, but indicated fine‐scale albedo feedbacks at depths of ~60 mm contributed to conditioning surface topography. We found profile‐based and two‐dimensional estimates of roughness revealed temporal change, and the aerodynamic roughness parameter, z0, showed a 22–32% decrease from ~1 mm following the exposure of bare‐ice, and a subsequent 72–77% increase. Using geostatistical techniques, we identified 'hole effect' properties in the surface elevation semivariograms, and demonstrated that hydrological drivers control the plot‐scale topography: degradation of superimposed ice reduces roughness while the inception of braided rills initiates a subsequent development and amplification of topography. Our study presents an analytical framework for future studies that interrogate the coupling between ice surface roughness and hydro‐meteorological variables and seek to improve parameterizations of topographically evolving bare‐ice areas. Abstract : We employ time‐lapse photogrammetry to quantify plot‐scale topographic evolution on a High‐Arctic glacier surface over the transition stage from seasonal snow cover to weathered bare‐ice. Using two‐dimensional geostatistical techniques, we reveal that hydrological drivers control the plot‐scale topography: degradation of superimposed ice initially reduces surface roughness, while the subsequent inception of braided rills activates the development and amplification of topography. We argue that our findings and analytical approach help advance the current understanding of glacier surface topographic evolution.